2016
DOI: 10.1159/000447506
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Rater Reliability of Neck Reflex Points in Women with Chronic Neck Pain

Abstract: Background: Neck reflex points (NRP) are tender soft tissue areas of the cervical region that display reflectory changes in response to chronic inflammations of correlated regions in the visceral cranium. Six bilateral areas, NRP C0, C1, C2, C3, C4 and C7, are detectable by palpating the lateral neck. We investigated the inter-rater reliability of NRP to assess their potential clinical relevance. Methods: 32 consecutive patients with chronic neck pain were examined for NRP tenderness by an experienced physicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In addition to the approaches used in a few reviewed exemplars, whole systems researchers may refer to a growing methodological literature in this area. 26,125,136…”
Section: Results Overviewmentioning
confidence: 99%
“…In addition to the approaches used in a few reviewed exemplars, whole systems researchers may refer to a growing methodological literature in this area. 26,125,136…”
Section: Results Overviewmentioning
confidence: 99%
“…19 Previous research has indicated a significant reduction in the sensitivity of the trapezius region in patients with chronic neck pain, trapezius tension, and chronic pharyngeal irritation after receiving bilateral submucosal injections of 0.5 mL of 1% procaine in the pharyngeal region. 31 We identified several case reports on the therapeutic effects of LA injections in patients with chronic pain, in addition to their anesthetic effects. [13][14][15]17,32 Nociceptive processes cause a reflex response that is largely mediated by sympathetic nerves and involves changes in blood flow, increased skin turgor and muscle tone, hyperalgesia in localized areas of the skin, and organ dysregulation at corresponding dermatome levels.…”
Section: Discussionmentioning
confidence: 99%
“…The objective is the generation of a directed stimulus (through the needle) and the selective extinction of other stimuli (through the LA), thus affecting the nervous system and tissue perfusion [15] and allowing the interruption of positive feedback loops (vicious circles) of pain and other pathological processes [12, 13, 15]. The treatment modalities in NT are local therapy (injection in trigger points and in areas of tension or pain on palpation) [16]; segmental therapy (injection in reflex areas of HEAD, sympathetic ganglia, nerve roots, or peripheral nerves) [12, 13]; and interference field therapy (injection into areas of chronic alteration of a structure of the organism that can cause or maintain a symptomatic alteration in another area of the organism) [10, 12, 13].…”
Section: Introductionmentioning
confidence: 99%